(untitled) (Bangladesh Journal of Agricultural Research, 2013)
Twelve commercial and promising mango cultivars were evaluated at three agroecological zones of Bangladesh viz., Akbarpur (AEZ 29), Chapai Nawabgonj (AEZ 11), and Gazipur (AEZ 28) during 2006-07 to investigate their regional adaptability. Cultivars included in the experiment were Ashwina, BARI Aam-1, Bombai, Deori, Fazli, Gopalbhog, Kalia, Khirsapat, Langra, Lata Bombai, Rani Passand, and Surjapuri. The plants were transplanted in the field during July 1993. Tree volume was the maximum (79.78 m3) in Khirsapat and the minimum in Lata Bombai (21.92 m3). Langra had the highest percentage of perfect flower (27%), while the lowest was in Deori and Kalia (5%). The earliest and latest fruit was harvested from BARI Aam-1 and Ashwina, respectively, at all locations. All the cultivars were harvested 3-5 and 8-10 days earlier at Akbarpur and Gazipur, respectively, compared to that at Chapai Nawabgonj. The highest individual fruit weight was obtained from Fazli at all locations, while Gopalbhog (130 g) had the lowest fruit weight at Akbarpur and Surjapuri at Chapai Nawabgonj (172 g) and Gazipur (140 g). Total soluble solids content was reasonably high in all the cultivars at each location (around 20%) except Ashwina, Lata Bombai, and Surjapuri which contained around 16% TSS. Lata Bombai was highly susceptible to anthracnose, floral malformation, and stem-end-rot at almost all the locations. Other cultivars showed low to medium susceptibility to all these diseases. The highest and lowest fruit producing cultivars were Khirsapat (206) and Lata Bombai (106) at Gazipur, while Rani Passand (196) and Bombai, Lata Bombai (92) at Akbarpur but at Chapai Nawabgonj, these were Langra (325) and Deori (117), respectively. Cultivar Fazli (83.61 kg) was the highest yielder by weight, while Lata Bombai (18.35 kg) was the lowest. Among the locations, Chapai Nawabgonj was the most favourable for plant growth, perfect flower production, and yield, and least favourable for pests and diseases. The overall result of the experiment indicated that good quality mango could also be grown successfully under Akbarpur and Gazipur conditions adopting appropriate variety like Khirsapat. DOI: http://dx.doi.org/10.3329/bjar.v37i4.14394 Bangladesh J. Agril. Res. 37(4): 691-710, December 2012